EBM II: How to perform a literature search. Issue 3 (May 2019) - Castagnetti, M.; Herbst, K.W.; Bagli, D.; Beckers, G.M.A.; Harper, L.; Kaefer, M.; Kalfa, N.; Fossum, M.
Summary: The present article is a second part related to evidence based medicine (EBM) in a series of five by the European society for paediatric urology (ESPU) research committee. It will present the different databases/search engines available to clinicians and researchers and describe strategies to focus the search to one's particular needs. Indeed, databases/search engines used and search strategy should vary according to the goal of the research. If the aim is to address a clinical problem, the search should allow to identify a small number of most pertinent articles (high specificity); if the search is for research purposes, instead, it should ensure no meaningful articles are overlooked (high sensitivity).